(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2012)
In the era of global warming and increasing urban heat island condition, flat concrete deck on shop-houses may be less sustainable to handle the excessive solar heat radiation impacts on the roof surfaces. Innovative alternative roofing system is needed to manage heat radiation that will lead to sustainable factors likes energy savings, less energy body used on the roofing materials, and provide comprehensive environmental friendly roof system. This paper discusses about particular environmental friendly materials such as “Pakis-Stem Blocks” system is a good thermal resistant to absorb the solar sun heat and provide natural cooling through convective-wind without adding substantial loads to the roof structures. “Pakis-stem blocks” are easier, cheaper and more valuable than other sub-structure roofing materials as thermal resistant layer on flat bare concrete deck besides green roofing systems.